2012
DOI: 10.1099/vir.0.038992-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane targeting of an alpha-like tetravirus replicase is directed by a region within the RNA-dependent RNA polymerase domain

Abstract: The members of the family Tetraviridae are small positive-sense insect RNA viruses that exhibit stringent host specificity and a high degree of tissue tropism, suggesting that complex virus-host interactions are likely to occur during infection and viral replication. The alpha-like replicase of Helicoverpa armigera stunt virus (HaSV) (genus Omegatetravirus) has been proposed to associate with membranes of the endocytic pathway, which is similar to Semliki Forest virus, Sindbis virus and rubella virus. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These biochemical features indicate that DpTV Hel should function in a limited environment in cells. Indeed, RNA replication of ( þ)RNA viruses requires viral RNA replicase proteins to associate with intracellular membranes and induce membrane invagination to form small spherules (Ahlquist, 2006;Short and Dorrington, 2012;Short et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These biochemical features indicate that DpTV Hel should function in a limited environment in cells. Indeed, RNA replication of ( þ)RNA viruses requires viral RNA replicase proteins to associate with intracellular membranes and induce membrane invagination to form small spherules (Ahlquist, 2006;Short and Dorrington, 2012;Short et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of RNA virus studies in Lepidoptera is limited compared to DNA virus studies and largely restricted to non-enveloped dsRNA and (+)-sense ssRNA viruses such as cypoviruses (Hill et al, 1999), iflaviruses (van Oers, 2010) and tetraviruses (Short and Dorrington, 2012). These viruses only infect invertebrate hosts and several cannot productively replicate in cultured cells (Short and Dorrington, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of RNA virus studies in Lepidoptera is limited compared to DNA virus studies and largely restricted to non-enveloped dsRNA and (+)-sense ssRNA viruses such as cypoviruses (Hill et al, 1999), iflaviruses (van Oers, 2010) and tetraviruses (Short and Dorrington, 2012). These viruses only infect invertebrate hosts and several cannot productively replicate in cultured cells (Short and Dorrington, 2012). Furthermore, to our knowledge, (−)-sense ssRNA viruses have not been previously reported to eLife digest Viruses can infect species as diverse as bacteria, plants and animals, and once they have infected an organism they hijack its cells to rapidly replicate their own genetic material, which is made of DNA or RNA.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative topological structural analysis based on TBSV p92 transmembrane topology (Scholthof et al, 1995) showed that the two transmembrane topology model for PrV p104 was likely since it positioned all functional motifs and domains within the cytosolic side of the membrane. The putative transmembrane helix, TM1 (52 -72) and TM2 (225 -247) located at the N-terminus of p40 would traverse the lipid membrane twice, just like in TBSV p92, and provide membrane anchorage, a prediction supported by the association of PrV replication proteins with detergent resistant membranes in vivo (Short and Dorrington, 2012). The two transmembrane helix found in PrV consist of 20 and 22 amino acids respectively and are comparable to those belonging to plant protein, TBSV p92, 15 and 22 amino acids respectively.…”
Section: Discussionmentioning
confidence: 97%